Sriwijaya period ceramics found in the Musi River as a learning source for Palembang local history - Sholeh, Kabib; Warto, Warto; Djono, Djono (LPMPP Universitas Negeri Yogyakarta, 2025)
This study addresses the limited understanding and integration of archeological findings, specifically the Srivijaya-period ceramics discovered in the Musi River in Palembang, Indonesia, into historical education. Although these findings hold significant historical importance, their incorporation into the historical education curriculum remains limited, thereby hindering the potential for enriching historical knowledge and fostering local cultural identity. Employing qualitative descriptive approach, this research aims to explore the historical value of Sriwijaya period ceramics from the Musi River and their integration as a source for learning local history in Palembang. Its data was collected through literature study, document analysis, and field observations. The literature study includes historical and archaeological references related to the Sriwijaya Kingdom and ceramics found in the Musi River, and the document analysis entails examining archaeological finds and previous research reports. The data were then analyzed to reveal the historical value of ceramics and their potential as a source of learning the history of Palembang. The identification of Chinese ceramic artifacts from the Sriwijaya era has yielded ceramics from the Tang (7th-9th century AD) and Sung (10th-13th century AD) dynasties. The discovery of these artifacts holds historical significance in the domains of foreign policy, economics, social, and cultural development during the flourishing of Sriwijaya in Palembang, and these can serve as a valuable resource for local history education in schools.